Xenon Anesthesia Improves Respiratory Gas Exchanges in Morbidly Obese Patients. (4th February 2010) - Abramo, Antonio; Di Salvo, Claudio; Foltran, Francesca; Forfori, Francesco; Anselmino, Marco; Giunta, Francesco
Abstract : Background . Xenon-in-oxygen is a high density gas mixture and may improve PaO2/FiO2 ratio in morbidly obese patients uniforming distribution of ventilation during anesthesia. Methods . We compared xenon versus sevoflurane anesthesia in twenty adult morbidly obese patients (BMI > 35 ) candidate for roux-en-Y laparoscopic gastric bypass and assessed PaO2/FiO2 ratio at baseline, at 15 min from induction of anaesthesia and every 60 min during surgery. Differences in intraoperative and postoperative data including heart rate, systolic and diastolic pressure, oxygen saturation, plateau pressure, eyes opening and extubation time, Aldrete score on arrival to the PACU were compared by the Mann-Whitney test and were considered as secondary aims. Moreover the occurrence of side effects and postoperative analgesic demand were assessed. Results . In xenon group PaO2-FiO2 ratio was significantly higher after 60 min and 120 min from induction of anesthesia; heart rate and overall remifentanil consumption were lower; the eyes opening time and the extubation time were shorter; morphine consumption at 72 hours was lower; postoperative nausea was more common. Conclusions . Xenon anesthesia improved PaO2/FiO2 ratio and maintained its distinctive rapid recovery times and cardiovascular stability. A reduction of opioid consumption during and after surgery and an increased incidence of PONV were also observed in xenon group.